2019
DOI: 10.1177/2158244018821757
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Factors for Success as an Online Entrepreneur in Thailand

Abstract: This research aims to study the success factors of an online entrepreneur. With the recent rapid growth of the online market for different goods and services, the need to investigate the business strategy of online entrepreneurs in specific markets such as in Thailand and extract relevant success factors is dire. The researcher collected data by using a seven-point Likerttype scale that measured the responses of 180 online businesses in Bangkok, Thailand. The study used Structural Equation Modeling (SEM) and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The available technological advantages have been considered the most fundamental factor in evaluating the external environment of ventures. Available technological advantages can lead to innovative behavior because they provide new product and services (Nasution & Mavondo, 2008) that ultimately enhance a venture's performance (Olbrich et al, 2017;Phonthanukitithaworn et al, 2019). Long et al (2018) studied different kinds of success factors and suggested that continual expansion and progress is important for the sustainability of firms.…”
Section: Internal and External Environment And Wobsmentioning
confidence: 99%
See 1 more Smart Citation
“…The available technological advantages have been considered the most fundamental factor in evaluating the external environment of ventures. Available technological advantages can lead to innovative behavior because they provide new product and services (Nasution & Mavondo, 2008) that ultimately enhance a venture's performance (Olbrich et al, 2017;Phonthanukitithaworn et al, 2019). Long et al (2018) studied different kinds of success factors and suggested that continual expansion and progress is important for the sustainability of firms.…”
Section: Internal and External Environment And Wobsmentioning
confidence: 99%
“…Gupta and Mirchandani (2018) argued that government support significantly contributes to the success of women-owned SMEs. Government support also positively affects an online entrepreneur's success (Phonthanukitithaworn et al, 2019). Due to the huge contributions of WOB to the overall economic growth and development, the available government support should be evaluated to see how it affects business performance.…”
Section: Supportive Factors and Performance And Wobsmentioning
confidence: 99%
“…Policy support is an important driving force of the new economy and I&E activities, especially within the context that most cities have introduced numerous preferential policies. The relative attractiveness of policies is an important aspect for local new economy development (Phonthanukitithaworn et al, 2019). This study evaluates policy support by three indicators: the strength of local government's support to the new economy, the institutional construction situation of the management organization of the new economy, and the proportion of science and technology expenditure in public finance.…”
Section: Statistical Yearbooks and Bulletins Of The Citiesmentioning
confidence: 99%
“…Therefore, if the number of words related to the new economy mentioned in the report is more, the local government will pay more attention to the development of the new economy, and enterprises will change their strategic behaviors in response to governmental orientation (Y. Ding et al, 2016;Phonthanukitithaworn et al, 2019).…”
Section: Statistical Yearbooks and Bulletins Of The Citiesmentioning
confidence: 99%
“…Based on figure 1, to be an entrepreneur, everyone can be influenced by many factors, namely education, family, environment, friend, and so on. Phonthanukitithaworn, Ketkaew, & Naruetharadhol (2019) research that studied the successful factors of an online entrepreneur in Bangkok, Thailand showed that thirteen of the most relevant factors related to online entrepreneurs were ACO, EOU, government support, networks, risk-taking tendencies, reliability, AFF, BIM, logistics and transportation, quality products, product prices, advertisements on social media, and staff and employees.…”
Section: The Forming Of the Entrepreneurial Spirit Through Student Comentioning
confidence: 99%